Incorporating global change reveals extinction risk beyond the current Red List - Peng, Shijia; Shrestha, Nawal; Luo, Yuan; Li, Yaoqi; Cai, Hongyu; Qin, Haining; Ma, Keping; Wang, Zhiheng (Current Biology, 2023)
Summary Global changes over the past few decades have caused species distribution shifts and triggered population declines and local extinctions of many species. The International Union for Conservation of Nature (IUCN) Red List of Threatened Species (Red List) is regarded as the most comprehensive tool for assessing species extinction risk and has been used at regional, national, and global scales. However, most Red Lists rely on the past and current status of species populations and distributions but do not adequately reflect the risks induced by future global changes. Using distribution maps of >4,000 endemic woody species in China, combined with ensembled species distribution models, we assessed the species threat levels under future climate and land-cover changes using the projected changes in species’ suitable habitats and compared our updated Red List with China’s existing Red List. We discover an increased number of threatened species in the updated Red List and increased threat levels of >50% of the existing threatened species compared with the existing one. Over 50% of the newly identified threatened species are not adequately covered by protected areas. The Yunnan-Guizhou Plateau, rather than the Hengduan Mountains, is the distribution center of threatened species on the updated Red Lists, as opposed to the threatened species on the existing Red List. Our findings suggest that using Red Lists without considering the impacts of future global changes will underestimate the extinction risks and lead to a biased estimate of conservation priorities, potentially limiting the ability to meet the Kunming-Montreal global conservation targets.
Keywords: extinction; global change; Kunming-Montreal global conservation targets; Red List; threat level; threatened species